PENERAPAN MODEL PEMBELAJARAN MASTER TERHADAP KEMAMPUAN PEMAHAMAN KONSEP SISWA DI SMA N 1 DORO - Azizah, Dewi; Innayah, Rizka; Mardhiyana, Dewi (JURNAL LITBANG KOTA PEKALONGAN, 2019)
The efforts of teachers to improve students 'ability to understand concepts are to package mathematics learning into learning that can foster students' motivation and passion for learning. The selection of the right learning model by the teacher can make learning effective and fun. One alternative learning model that makes students learn mathematics is fun is the MASTER lesson. This study aims to determine whether students' conceptual comprehension abilities with MASTER learning models are better than PBL learning models. This research is a quantitative research with a form of experimental design that is quasi experimental design .The population in this study were all students of class XI IPS SMA N 1 Doro in the academic year 2017/2018. The data collection methods used in this study are of two kinds, namely interviews and tests. The method of data analysis in this study used the t test. Before the t test, the prerequisite test is first, namely normality and homogeneity test. Based on the calculation of the t test, the results obtained that t value of tcount = 2.133 and t0.025; 39 = 2.023, so that tcount> t0.025; 39 then Ho is rejected. This means that the MASTER learning model produces a better understanding ability of concepts than the PBL learning model. Keywords: MASTER, PBL, Concept understanding ability